Understanding the weakness in global trade - What is the new normal? - Bruno Cabrillac; Alexander Al-Haschimi; Oxana Babecká Kucharčuková; Alessandro Borin; Matthieu Bussière; Raphael Cezar; Alexis Derviz; Dimitra Dimitropoulou; Laurent Ferrara; Martin Gächter; Guillaume Gaulier; Juhana Hukkinen; et al. (European Central Bank (ECB), 2016)
Global trade has been exceptionally weak over the past four years. While global trade grew at approximately twice the rate of GDP prior to the Great Recession, the ratio of global trade to GDP growth has declined to about unity since 2012. This paper assesses to what extent the change in the relationship between global trade and global economic activity is a temporary phenomenon or constitutes a lasting change. It finds that global trade growth has been primarily dampened by two factors. First, compositional factors, including geographical shifts in economic activity and changes in the composition of aggregate demand, have weighed on the sensitivity of trade to economic activity. Second, structural developments, such as waning growth in global value chains, a rise in non-tariff protectionist measures and a declining marginal impact of financial deepening, are dampening the support from factors that boosted global trade in the past. Notwithstanding the particularly pronounced weakness in 2015 that is assessed to be mostly a temporary phenomenon owing to a number of country-specific adverse shocks, the upside potential for trade over the medium term appears to be limited. The “new normal” for global trade can therefore be expected to look broadly similar to the weakness observed over recent years on average. In this sense, buoyant trade dynamics in the 1990s and early 2000s may have been what was exceptional, rather than the slowdown over recent years.
Keywords: F10; F13; F14; F15; 330; frictions in global trade; global trade slowdown; global value chains; protectionism; trade elasticity